Changes in lumbopelvic motion and trunk muscle activity during 2000 m rowing ergometer trial - Sekine, C.; Matsunaga, N.; Kaneoka, K. (International Journal of Sport & Health Science, 2021)
The changes in lumbopelvic motion and trunk muscle activity occurring during 2000 m rowing in elite collegiate rowers (five men and three women with rowing careers of 5.6±2.1 years) were investigated. The pelvic inclination and the lumbar angle were calculated. Surface electrodes were attached to the rectus abdominis, external oblique, internal oblique, multifidus, erector spinae, latissimus dorsi, rectus femoris, and biceps femoris. Three consecutive strokes at the 20% and 80% time-points of a 2000 m race simulation were analyzed. The root-mean-square was calculated during the early drive phase, late drive phase, and recovery phase. Root-mean-square amplitude was normalized by maximum voluntary contraction. Between two time-points, paired t-tests for each angle and Wilcoxon signed-rank tests for each muscle were performed.